The impact of financial factors on monetary policy responses in emerging market economies - Ali İlhan (Ekonomski Vjesnik, 2023)
Purpose: This study investigates the monetary policy responses of emerging market inflation targeters to financial factors both before and after the 2008 global financial crisis (GFC). Methodology: Taylor rules, augmented with the nominal exchange rate, the exchange market pressure index, and the U.S. federal funds effective rate, are analyzed by using the augmented mean group (AMG) panel estimator for 12 emerging market economies (EMEs) that adopted an inflation targeting regime. The sample is divided into two periods around the GFC: 2002Q1-2007Q4 and 2010Q1-2019Q4. Results: Inflation significantly and positively impacted interest rate settings during both periods. The panel AMG results indicate that the EMEs’ responses to financial variables only had a significant effect during the post-crisis period, while the federal funds effective rate had the most impact among the financial variables. The country-specific results indicate that some central banks also reacted to financial variables before the GFC. Conclusion: Inflation played an important role in policy rate decisions for both periods despite the slightly decreasing weight in interest rate settings after the GFC due to the increasing influence of financial variables. Although financial variables were important in setting interest rates during both periods, the EMEs’ post-GFC monetary policies focused more on financial stability. Furthermore, their monetary policies became more compatible with external financial conditions after the GFC.